RAGE in the pathophysiology of skeletal muscle. Issue 7 (18th October 2018) - Riuzzi, Francesca; Sorci, Guglielmo; Sagheddu, Roberta; Chiappalupi, Sara; Salvadori, Laura; Donato, Rosario
Abstract: Emerging evidence suggests that the signalling of the Receptor for Advanced Glycation End products (RAGE) is critical for skeletal muscle physiology controlling both the activity of muscle precursors during skeletal muscle development and the correct time of muscle regeneration after acute injury. On the other hand, the aberrant re‐expression/activity of RAGE in adult skeletal muscle is a hallmark of muscle wasting that occurs in response to ageing, genetic disorders, inflammatory conditions, cancer, and metabolic alterations. In this review, we discuss the mechanisms of action and the ligands of RAGE involved in myoblast differentiation, muscle regeneration, and muscle pathological conditions. We highlight potential therapeutic strategies for targeting RAGE to improve skeletal muscle function.